Whole-Genome Sequencing of Klebsiella pneumoniae Isolates to Track Strain Progression in a Single Patient With Recurrent Urinary Tract Infection - Wylie, Kristine M.; Wylie, Todd N.; Minx, Patrick J.; Rosen, David A. (Frontiers in Cellular and Infection Microbiology, 2019)
Klebsiella pneumoniae is an important uropathogen that increasingly harbors broad-spectrum antibiotic resistance determinants. Evidence suggests that some same-strain recurrences in women with frequent urinary tract infections (UTIs) may emanate from a persistent intravesicular reservoir. Our objective was to analyze K. pneumoniae isolates collected over weeks from multiple body sites of a single patient with recurrent UTI in order to track ordered strain progression across body sites, as has been employed across patients in outbreak settings. Whole-genome sequencing of 26 K. pneumoniae isolates was performed utilizing the Illumina platform. PacBio sequencing was used to create a refined reference genome of the original urinary isolate (TOP52). Sequence variation was evaluated by comparing the 26 isolate sequences to the reference genome sequence. Whole-genome sequencing of the K. pneumoniae isolates from six different body sites of this patient with recurrent UTI demonstrated 100% chromosomal sequence identity of the isolates, with only a small P2 plasmid deletion in a minority of isolates. No single nucleotide variants were detected. The complete absence of single-nucleotide variants from 26 K. pneumoniae isolates from multiple body sites collected over weeks from a patient with recurrent UTI suggests that, unlike in an outbreak situation with strains collected from numerous patients, other methods are necessary to discern strain progression within a single host over a relatively short time frame.